The molecular mechanisms and new classification of resistant starch – A review - Haixia Zhong; Zhiguang Chen; Yong Han; Ke Hu (Current Research in Food Science)
Diabetes is one of the major chronic diseases endangering human health. Because of the low glycemic index, RS(resistant starch) plays an important role in the intervention and treatment of diabetes. Based on our previous studies, the mechanism of RS is systematically discussed from the molecular level (the relationship between starch molecular conformation and RS, the relationship between double-helix structure and RS, and the relationship between molecular complexation and RS) and granular level (the relationship between amylase penetration and RS, the relationship between crystallinity and RS, and the relationship between amylose/amylopectin content and RS). In addition, with more in-depth studies in the preparation and formation reason of RS, the current classification of RS may not satisfy our current understanding of RS. In this paper, a new classification of RS is proposed. RS is classified into 10 types from two aspects (reparation methods and formation reasons), which may make it easier to understand the different RS. This paper may provide a reference for the research of RS.